(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Government of Mongolia has developed “National Development Strategy of Mongolia” and “Regional Development Policy of Mongolia” and it was focused on promoting fast development of tourism as one of the leading sectors of the economy. Furthermore, increase in responsibility of state and local authorities for business sector is paying more attention to further development of regional tour-recreation. Given that the tour-recreation recourses in rural area are ought to be determined specifically as well as the determined recourses are required to be utilized in efficient way, it is envisaged that gradually increases are important for involving the Camp of cooperating Herding Households (CCHH) to be participated in local tour-recreation activities. Accordingly, demands are raised to identify the factors and influences on developing the Tour-recreation activities in CCHH. Our objective of this research work is to conduct the full assessment and regionalize the tour-recreational capacity of Uvs province. Journal of agricultural sciences №15 (02): 130-133, 2015